PENEMUAN HUKUM (RECHTSVINDING) DAN PENCIPTAAN HUKUM (RECHTSSCHEPPING) OLEH HAKIM UNTUK MEWUJUDKAN KEADILAN - Siti Malikhatun Badriyah (Masalah-Masalah Hukum, 2011)
At present, the judge should have high creativity and progressive minded, so it really enforce the law in accordance with the values a a that develop within the society. In judging and decision making, judges must conduct rechtsvinding, so that decisions can actually bring about justice for the coveted society. In Jaw enforcement judges should adhere to the principle that the law is for man, not man for the law, so it should really pay attention to the dynamics of society. Judges no longer a la Bouche de la loi (funnel legislation), but also conduct rechtsvinding of rechtsschepping even if the decision followed the other judges in decisionmaking. Thus, the judge should have as a vigilante or a mujtahid (one who fought jihad), which can reveal the hidden force of law, so the law becomes sharp and can solve problems in society.